Seroprevalence and risk factors analysis of hepatitis E virus infection in human population from Tandil, Buenos Aires, Argentina - Rivero, Mariana Alejandra (2022)
Background: Hepatitis E virus (HEV) infection is a common cause of acute clinical hepatitis worldwide and an emerging disease in Argentina, primarily transmitted via the fecal-oral route due to contaminated water and food. It is also a zoonotic disease, being swine the main reservoir. Prevalence of HEV infection in humans in several regions of Argentina remains unknown, mainly because of lack of awareness and proper diagnosis.Objectives: i) to determine the prevalence of HEV infection in humans from Tandil; ii) to evaluate its association with demographic and socioeconomic variables, and iii) to describe and analyze spatial patterns related to the infection. Methods: Blood samples were obtained from 969 individuals aged 1-80 years (median 44) by a random spatial sampling method. Socioeconomic information (socioeconomic status, overcrowding, educational level, health insurance coverage, access to drinking water, and appropriate sewage disposal) was obtained by a survey. The address of the participants was georeferenced. Anti-HEV IgG was detected by a validated indirect in-house ELISA, developed in INSIBIO (CONICET-UNT). Associations between the variables and seropositivity were evaluated by Chi square and Wilcoxon tests. Scanning for clusters with high rates of positivity was carried out using the Bernoulli model.Results: Anti-HEV antibodies were detected in 4.34% (IC 95% 3.23-6.01) of samples, more frequently in men (6%) than women (4%), although not statistically significant (p-value 0.0542). The median age of seropositive individuals was higher than seronegative (52 vs 42, p-value 0.0002). Socioeconomic variables were not associated with seropositivity. No significant cluster of positivity was detected by the purely spatial analysis.Conclusions: HEV is prevalent in the population under study. The importance of considering HEV infection in the differential diagnosis of hepatitis in inhabitants belonging to different socioeconomic groups is highlighted.